Clinical impact of ceruloplasmin levels at ANCA-associated vasculitis diagnosis - Camboulive, Louis; Grandhomme, Frédérique; Martin Silva, Nicolas; Khoy, Kathy; Mariotte, Delphine; Lobbedez, Thierry; Dumont, Anaël; Nguyen, Alexandre; de Boysson, Hubert; Aouba, Achille; Deshayes, Samuel (PLOS ONE, 2024)
Objectives Ceruloplasmin is an inhibitor of myeloperoxidase (MPO) activity that plays an important role in the pathophysiology of anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV). This study aimed to evaluate the prognostic impact of serum level of ceruloplasmin at diagnosis in patients with anti-MPO antibody-positive AAV. Methods This retrospective monocentric study in Caen University Hospital involved all consecutive adult anti-MPO antibody-positive patients with microscopic polyangiitis or granulomatosis with polyangiitis, diagnosed between January 2010 and January 2022 with available serum sample at inclusion. Patients outcomes were analyzed from two subgroups constituted according to the median serum level of ceruloplasmin. The same analyses were then performed in anti-proteinase 3 (PR3) antibody-positive patients. Results Within the 92 patients analyzed, 50 patients had anti-MPO antibodies with a median ceruloplasmin level of 0.44 [quartiles 1–3, 0.40–0.49] g/L and a median Birmingham Vasculitis Activity Score of 19 [14–22]. After a median follow-up period of 40 [22–86] months, 13 (26%) patients had died: 10 (40%) in the low ceruloplasmin group and 3 (12%) in the high ceruloplasmin group (p = 0.03), with a significantly worse survival rate in the low ceruloplasmin group (p = 0.021). No significant differences in relapse rate or renal failure was observed between the two groups. The same analyses performed in the group of AAV patients with anti-PR3 antibody did not show any differences. Conclusion In anti-MPO AAV patients, serum level of ceruloplasmin at diagnosis seems to be associated with a significant impact on survival.